LOGISTICS OF PUBLIC PROCUREMENT IN FOREIGN COUNTRIES (ON THE EXAMPLE OF USA, GERMANY AND POLAND) - A, Toluev Yuri; A, Mukhtarova Karlygash; A, Mukhtar Yernur; A, Akhmetkaliyeva Sandigul; A, Kozhakhmetova Assel (Farabi Journal of Social Sciences, 2019)
Abstract. Issues of regulating public procurement throughout the world are the subject of close attention from the legislators. Because in this case the buyer in the face of the state is interested in the maximum efficiency of the process. One of the important directions in lawmaking around the world has become the struggle for fair competition, which, according to economic theory, should lead to lower prices. The main problem in the modern practice of public procurement is the “human factor”, which generates corruption and bad faith. This isn`t about episodic bribing of officials, but about the merging of government and business, as a result of which, along with competitive methods of selecting suppliers, lobbying has become important. However, it is believed abroad that a well-developed regulatory framework and competent procurement administration may well reduce potential efficiency losses to a minimum (Government purchases abroad, 2017). The purpose of the study is to consider the theory and practice of public procurement management in developed countries, such as the United States, Germany and Poland, which have many years of specific experience in regulating public procurement, in addition, highlighting the most important aspects of state order placement in Kazakhstan Republic from the scientific research viewpoint. Key words: government procurement, government order, government regulation, public procurement system, logistics, legislation effectiveness, suppliers, government and business, corruption, competition, price policy, foreign practice.